Effectiveness of lactation counseling on maintenance of breastfeeding - hasan, Rajaa; abbas, Iqbal (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To determine the effectiveness of lactation counseling on maintenance of breastfeeding aftercesarean section for study group.Methodology: A quasi-experimental study was conducted on non probability sample (purposive) of (60) womenwho had cesarean section and sample divided in to two groups (30) of them as a study group from Fatima AlZahra'aMaternity and Pediatric Teaching Hospital & implement lactation counseling on it and another group (30)as control group from Baghdad Teaching Hospital in Baghdad City. Study implemented for the period of April 24th2011 to August 2nd 2011. A questionnaire was used as a tool of data collection to fulfill with objective of the studyand consisted of three parts, including demographic, reproductive characteristics and maintenance ofbreastfeeding of the sample. A pilot study was carried out to test the reliability of the questionnaire and contentvalidity was carried out through the 11 experts. Descriptive and inferential statistical analyses were used toanalyze the data.Results: The results of the study revealed that most mothers their ages within ideal fertility age which rangedbetween (20-24) years, and most of them had low educational level, and were housewives, and live in urbanarea, with moderate socioeconomic status, and (53.3%), (50%) respectively of them were primigravida. Thestudy shows that (100%) of the study group had continued breastfeeding, while (76.7%) of the control group hadcontinued breastfeeding and the reasons for discontinuation of breastfeeding for control group are not enoughmilk and newborn refuse lactation, (73.3%) of the study group had exclusive breastfeeding, while (26%) of thecontrol group had exclusive breastfeeding.Recommendations: The study recommended to reactivate the role of Baby-Friendly Hospitals Initiative inpromoting of breastfeeding by implementation of ten steps successful of breastfeeding, and breastfeedingcounseling for women during pregnancy and after birth especially who have cesarean section which has importantrole on maintenance of breastfeeding up to 6 months after birth.